The criterion of significance of general adaptive ability: numerical model - E. S. Rekashus; O. V. Kurdakova (Аграрная наука Евро-Северо-Востока, 2018)
The aims of the study: 1) to give an example of calculating the criterion for evaluation the collection of air-dry matter of the new red clover variety (Trifolium pratense L.) Pochinkovets in a competitive variety test; 2) to compare the general adaptive ability (GAA) of the selection achievement with other evaluation criteria. The initial data for the statistical processing were obtained from 2013 to 2015 in the breeding crop rotation of the Smolensk State Agricultural Experimental Station named after A.N. Engelhardt. The soil of test plots is sod-medium podzol light loamy with a medium acidic reaction, low content of humus, high content of mobile phosphorus and medium mobile potassium level. The wintering conditions varied from favorable to causing snow cover fracture, with low negative temperatures effect coming next. The vegetative periods were characterized by an elevated temperature. The moisture regime varied from optimal to semi-arid. Four selective numbers were tested: Pochinkovets variety (S-434), S-439, R-4 (from Smolensk State Agricultural Experimental Station named after A.N. Engelhardt) and No. 359 (France). The variety Smolensky 29 was the standard. The least significant difference in GAA at alpha level of 0.05 was 0.49 t/ha of air-dry matter. Two selective numbers were chosen. They are S-434 (Pochinkovets) and No. 359 (with GAA 0.92 and 0.83 t/ha of air-dry matter respectively). The GAA of the standard was 1.01 t/ha (significantly low). The S-434 (Pochinkovets) variety was more stable than No. 359. Its specific adaptive ability equal to 3.30 was lower than that of No. 359 (5.05). For this reason, the selection value of the genotype S-434 (Pochinkovets) equal to 4.88 was higher than that of No. 359 (3.00). Based on the positive results of the competitive test, the new Pochinkovets variety was passed to the State varietal test. Since 2018 it has been included into the State Register of Selection Achievements. The new statistical criterion was successfully tested during the red clover selection process.